HOW AUTONOMOUS CARS WILL INFLUENCE THE CAR INSURANCE MARKET - Pisano, Simone; Janeček, Martin; Bušta, Ondřej; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2020)
The car market has always been considered as a mature market, immune from the influence of the major external factors. However, nowadays, it has been going through a complete transformation caused by the introduction of ever more advanced self-driving technologies that will change the relations with the customers and how they will approach to the transportation market.As a result, the new technology will not influence only the car manufacturers and the customers but will, for the first time, affect a pool of new stakeholders such as technological companies, software houses other than regulators and consequently, in an even larger scale, the insurance sector.Insurance companies will see their business evolving at a faster pace than ever with lower profits in their old core business and new competitors entering their influence area. An increased awareness of this evolution will be fundamental for the players of this market that will have to understand how to face the coming revolution. The new challenge will be both on taking advantage of the new opportunities offered and, staying alert on keeping the profitability of the old businesses. To do so, the right expertise in the new technologies has to be boosted making possible the transition to the new technological paradigms.This paper aims to analyse every aspect of this evolution to predict the possible outcomes and to provide useful advices to the insurance companies on how to stay successfully in control of their business and how to expand their influence to the new boundaries of technological evolution. This research aims to gather a general knowledge on the implications of new technologies applied to cars and in-depth insights on the consequences of these new technologies for the insurance market.
To develop this topic, a Case study qualitative approach is applied, and the sources provided are from papers, data, and forecasts already available in the literature and, sometimes, indirectly related to the phenomenon of driverless cars. The paper is divided in five chapters. After an introduction on the current situation, the first chapter analyzes all the possible short-term implications of the new self-driving technologies deployed and the ones on track to be introduced on the near future. The second chapter, following a similar structure of the first one, looks deeper into the future analyzing the heavier impact that full self-driving technologies will have on the car market and on the car insurance industry. In the third chapter the issue of responsibility determination in claims with driverless cars is deeply analyzed. This issue is probably the most disrupting change for the insurance companies’ world and deserve to be very well understood in order to successfully overcome the transition to driverless cars. The fourth chapter analyzes the business model of some of the most innovative companies involved in the insurance world and will try to find the pros and cons of their innovations focusing on the possible application on a broader scale. The fully self-driving cars will, according to more and more experts, require more time than previously expected, the reasons for this growing skepticism in the development of the required technologies is listed in the fifth and last chapter. The results indicate that the insurance sector will rather be transformed by the coming of new driving paradigms and by all its secondary consequences. This paper provides to the insurance players an overview of the phenomenon and some hints to overcome it in the best of the ways.
Vedoucí práce: Martin Janeček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: quantitative economic analysis [obor dipl. práce]; diplomové práce; master's theses